PENGARUH BANK SYARIAH YANG DIKELOLA BERDASARKAN PRINSIP SYARIAH SERTA FITUR DAN FASILITAS PRODUK PERBANKAN SYARIAH TERHADAP MINAT MENABUNG MASYARAKAT DI SURABAYA - Bobby Raditya Priambodo; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the Effect of Compliance with Sharia Compliance Management and Sharia Banking Product Features and Facilities Against the Interests of Surabaya People in Saving in Islamic Banking. The research method used is a quantitative approach. This study uses primary data by distributing questionnaires. In this study the authors used a saturated sampling technique found in Non-Probability Sampling. The analysis techniques used are validity and reliability tests, classic assumption tests, hypothesis tests. Based on the results of the study indicate that there is a one-way relationship on several variables, namely sharia compliance and product features and facilities to save interest.Keywords: Sharia Complience, Sharia Banking Product Facilities, Sharia Banks